GUAM AS SEEN FROM AZERBAIJAN - POLUKHOV, Elhan (CENTRAL ASIA AND THE CAUCASUS, 2008)
The 21st century is revealing its new face to the world community: it is unipolar yet strives for multipolarity, raising numerous global and regional issues as it goes. Francis Fukuyama’s “end of history” brought up questions previously camouflaged by the political and historical processes, the answers to which should be sought not only in the reality created by the end of the Cold War, but also in the changed social, economic, and political lifestyle manifesting itself across the vast stretches of Eurasia. The bulwark of socialism (alias the Soviet Union) disappeared, leaving the states of the socialist bloc (particularly the former Soviet republics) to fend for themselves and cope with numerous problems single-handedly. The post-Soviet republics turned to historical archives to restore the memories of their independence to be able to move toward new sovereignties. Few in the newly emerging market and capitalist environment could boast of relevant practical skills and past experience. By the time the Soviet Union disintegrated, the fifteen Soviet republics had been living under approximately equal economic conditions but had different natural and human resources; their location on the world’s political and geographic map also differed, which explains the different degrees of interest the regional and world powers showed in them. Those newly independent states that attracted the attention of the leading geopolitical actors were guided by their ethnic, linguistic, religious, military-political, economic, and other preferences in their choice of new allies to fill the political and ideological void. At the same time, the centuries-long experience of living in a single political and economic expanse dominated first by czarism and later, in Soviet times, by the C.P.S.U. taught all the republican political elites to rely on the Kremlin when making all decisions. This bad habit did not allow them to carefully analyze the short- and long-term results of the steps they took as leaders of independent states. More than that, by the time the Soviet Union disintegrated, the republics were practically inseparable economically: the death of the common state disrupted the interconnected production cycle and cornered all players in the post-Soviet and some players in the post-socialist expanse.